Prospects of attracting the economic resources of the waters of the World Ocean to the economic activity of Ukrainian business (Economics and region, 2023)
The article is devoted to determining the place occupied by sea spaces in the structure of water resources of Ukraine. It is noted that much more attention is paid to their land-based components, which is due to the general disdain for the marine economy in our country at all levels of state and regional administration. At the same time, as world experience proves, the waters of the World Ocean are not only a stipule for numerous varieties of useful flora and fauna, an environment in which freight and passenger transportation is carried out. Thanks to the application of appropriate technologies, it serves as a powerful source of moisture that people use in everyday life and use in solving technological problems. Among them are mechanical processing of materials, construction, and so on. At the same time, it was emphasized that numerous resources are dissolved in the waters of the World Ocean, although they have different levels of concentration. Depending on it and at the current level of development of mining technologies, the mining of certain materials has been established in many coastal countries, and the search for methods to reduce the price of those that are already mined, and are considered promising, is not abating. To support this statement, the article contains the results of an analytical review of the practice of the leading maritime states. Examples of scientific research are given, the results of which have opened up the possibilities of using mineral resources and generating energy using the waters of the World Ocean. Most of them have been brought to the level of practical application by business. All this, according to the authors, convincingly proves that the neglect of the economic resources of sea water or too limited ideas about its involvement in economic circulation should be changed as soon as possible. The war will eventually end, but the water supply problems will not disappear with it. Most likely, they will get worse. The article presents the vision of the authors regarding the conditions, the creation of which could make up for what has already been lost, but not completely. It is about their economic, ecological and administrative components.
Keywords: economy; maritime economy; the World Ocean; economic resources; water supply; sustainable development; marine spaces; water resources management